Pediatric Medical Care System in China Has Significantly Reduced Abandonment of Acute Lymphoblastic Leukemia Treatment. Issue 3 (April 2015) - Zhou, Qi; Hong, Dan; Lu, Jun; Zheng, Defei; Ashwani, Neetica; Hu, Shaoyan
<x xml:space="preserve">Abstract</x> In this study, we have analyzed both administrative and clinical data from our hospital during 2002 to 2012 to evaluate the influence of government medical policies on reducing abandonment treatment in pediatric patients with acute lymphoblastic leukemia. Two policies funding for the catastrophic diseases and the new rural cooperative medical care system (NRCMS) were initiated in 2005 and 2011, respectively. About 1151 children diagnosed with acute lymphoblastic leukemia were enrolled in our study during this period and 316 cases abandoned treatment. Statistical differences in sex, age, number of children in the family, and family financial status were observed. Of most importance, the medical insurance coverage was critical for reducing abandonment treatment. However, 92 cases abandoning treatment after relapse did not show significant difference either in medical insurance coverage or in duration from first complete remission. In conclusion, financial crisis was the main reason for abandoning treatment. Government-funded health care expenditure programs reduced families' economic burden and thereby reduced the abandonment rate with resultant increased overall survival.